Peran Kepemimpinan Transformasional Pada Perilaku Kewargaan Organisasional Dengan Komitmen Afektif Sebagai Variabel mediasi - Paulina Presi; Prayekti Prayekti; Kusuma Candra Kirana (FE Program Studi Manajemen, 2022)
This study aims to examine whether affective commitment mediates the relationship between transformational leadership and organizational citizenship behavior. This research method uses quantitative descriptive and primary data using a questionnaire.This study took samples at Pengudi Luhur gantiwarno Junior High School, Klaten, Central Java. The sampling technique used purposive sampling. Data collection is done by sending a questionnaire via personal chat or via e-mail in the form of google form to the school. The data were analyzed using multiple linear regression analysis.The results of this study indicate that transformational leadership has a positive effect on affective commitment and transformational leadership has a positive effect on organizational citizen behavior and affective commitment has a positive effect on organizational citizen behavior.Keywords: Transformational Leadership, Affective Commitment and Organizational Citizenship Behavior.